2021
DOI: 10.1007/s00039-021-00557-5
|View full text |Cite
|
Sign up to set email alerts
|

On the variance of squarefree integers in short intervals and arithmetic progressions

Abstract: We evaluate asymptotically the variance of the number of squarefree integers up to x in short intervals of length $$H < x^{6/11 - \varepsilon }$$ H < x 6 / 11 - ε and the variance of the number of squarefree intege… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…We should mention a very recent work [3] of Ofir Gorodetsky, Kaisa Matomäki, Maksym Radziwiłł and Brad Rodgers, in which the range of validity for the asymptotic formula extends to q as small as x 5/11 , which far surpasses what we have here. On the other hand their results are proven only for prime q and their error term which corresponds to our first error term, not being their prime concern but being our main concern, is far weaker than what we have.…”
Section: Definementioning
confidence: 54%
See 2 more Smart Citations
“…We should mention a very recent work [3] of Ofir Gorodetsky, Kaisa Matomäki, Maksym Radziwiłł and Brad Rodgers, in which the range of validity for the asymptotic formula extends to q as small as x 5/11 , which far surpasses what we have here. On the other hand their results are proven only for prime q and their error term which corresponds to our first error term, not being their prime concern but being our main concern, is far weaker than what we have.…”
Section: Definementioning
confidence: 54%
“…On the other hand their results are proven only for prime q and their error term which corresponds to our first error term, not being their prime concern but being our main concern, is far weaker than what we have. We should in particular mention that we found our argument for Lemma 3.6 after looking over [3].…”
Section: Definementioning
confidence: 90%
See 1 more Smart Citation
“…Keating and Rudnick [23] studied this problem in a function field setting, connecting it with Random Matrix Theory, and suggested based on this work that (1.1) will hold for H ≤ X 1−ε . The best known result is [12], where it is shown that (1.1) holds for H ≤ X 6/11−ε unconditionally and H ≤ X 2/3−ε on the Lindelöf Hypothesis. In fact in [12] it is shown that even an upper bound of order √ H for H ≤ X 1−ε for all ε > 0 would already imply the Riemann Hypothesis.…”
mentioning
confidence: 99%
“…The best known result is [12], where it is shown that (1.1) holds for H ≤ X 6/11−ε unconditionally and H ≤ X 2/3−ε on the Lindelöf Hypothesis. In fact in [12] it is shown that even an upper bound of order √ H for H ≤ X 1−ε for all ε > 0 would already imply the Riemann Hypothesis.…”
mentioning
confidence: 99%